Rebozo Technique on Pain Intensity in the First Stage of the Active Phase and Length of Labor in Multigravida Mothers, Wanayasa District, Purwakarta Regency, Indonesia - Sari, Daris Yolanda (HM Publisher, 2024)
Background: Pain during the first stage of the active phase is one of the main obstacles in the labor process. The rebozo technique, a traditional technique from Mexico, has been proven to be effective in reducing labor pain. This study aims to determine the effectiveness of the rebozo technique on the intensity of pain in the first stage of the active phase and the duration of labor in multigravida mothers in Wanayasa District, Purwakarta Regency. Methods: This research used a quasi-experimental design with a pre-test and post-test with a control group design. The research sample was 60 multigravida mothers who were divided into two groups: the intervention group (n=30), who received the rebozo technique, and the control group (n=30), who received standard care. Pain intensity was measured using the visual analogue scale (VAS) and duration of labor was calculated from 4 cm of cervical dilatation to complete dilation. Results: The results showed that there was a significant difference in the intensity of pain during the first active phase between the intervention group and the control group (p=0.001). The mean pain intensity in the intervention group was lower than the control group (VAS: 4.2 ± 1.5 vs. 6.1 ± 1.8). There was no significant difference in length of labor between the two groups (p=0.123). Conclusion: The rebozo technique is effective in reducing the intensity of pain during the first active phase in multigravida mothers but has no effect on the length of labor.